Improving Cross-Sector Data Consistency. (Policy Papers; Policy Paper, 2013)
The objective of the paper is to inform Executive Directors of recent work undertaken by the Statistics Department (STA) to further enhance data consistency. STA works to promote high quality statistics as essential pre-requisites for the formulation of appropriate macroeconomic and financial policies. Such work supports IMF surveillance and goals that are articulated in Board papers pertaining to Data Provision to the Fund for Surveillance Purposes; the G-20/IMFC Data Gaps Initiative; and the Fund's Data Standards Initiatives. All these initiatives are motivated by the Executive Directors' interest in better and more consistent data. An important element of STA's work program is the project to improve crosssector data consistency. This project has focused on an initial set of countries that reflect the diverse nature of the IMF's membership, and on selected data series. Data inconsistencies across macroeconomic datasets (financial, government, external, and national accounts statistics) have been found to exist for most countries, regardless of their size and level of development. Such inconsistencies may arise from a variety of reasons, including methodological differences and different data vintages. The project has been favorably received by member countries and has enhanced cooperation at both the international and national levels. Indeed, because a number of agencies within a country may be involved in compiling macroeconomic statistics, the project has encouraged strengthened national inter-agency cooperation to resolve inconsistencies. In spite of ongoing efforts, many inconsistencies persist, and new inconsistencies may sometimes arise. A significant initial finding is that countries may face challenges in improving cross-sector data consistency. In particular, member country resource constraints often limit the scope of their work in the short- and medium-term. Next steps. The recent work undertaken by STA has yielded significant positive results in a relatively brief period of time. Therefore, next steps involve expanding this work to eventually cover all countries, and monitoring inconsistencies on an ongoing basis so that they are not allowed to persist without follow-up with countries.